Intervention for Human Rights in Europe - Matláry, Janne Haaland. author. aut Link
XVIII, 286 p.
Keywords: Values, in terms of human rights and democracy, have become important factors for individual state's participation in the international community. Janne Haaland Matláry, former Secretary of State in the Department of Foreign Affairs, Norway, explores the ethical and moral conflict between the international system and the rights of sovereign powers in cases such as Kosovo, Bosnia and Rwanda.